Impact of Coronavirus Disease 2019 (COVID-19) Outbreak Quarantine, Isolation, and Lockdown Policies on Mental Health and Suicide - Ganesan, Balasankar; Al-Jumaily, Adel; Fong, Kenneth N. K.; Prasad, Palak; Meena, Surendra Kumar; Tong, Raymond Kai-Yu (Frontiers in Psychiatry, 2021)
The novel coronavirus disease (COVID-19) pandemic has made huge impact on physical and mental health wellbeing of the people, and it is also causing number of deaths all over the world. To prevent the spreading of coronavirus, different types of public health measures (social isolation, quarantine, lockdowns, and curfews) have been imposed by governments. However, mental health experts warn that the prolonged lockdown, quarantine, or isolation will create as a “second pandemic” with more psychological issues and suicides. The quarantined or isolated people are suffering from various issues such as physical inactivity, mental heal health, economic and social problems. As SARS outbreak in 2003, there are number of suicides reported in this current COVID -19 pandemic-lockdown due to various factors such as social stigma, alcohol withdrawal syndrome, fear of COVID infection, loneliness, and other mental health issues. This paper provides an overview of risk factors causing suicide and possible solutions to prevent the suicide in this current COVID-19 pandemic.